Boosting MSME Taxpayer Compliance: E-Billing, E-Filing, and Reduced Tax Rates in Intako: Meningkatkan Kepatuhan Wajib Pajak UMKM: E-Billing, E-Filing, dan Tarif Pajak yang Dikurangi di Wilayah Intako - Ika Ayu Damayanti; Herman Ernandi (Academia Open, 2022)
This study investigates the influence of the E-Billing system, E-Filing system, and reduced final income tax rates on the compliance behavior of MSME taxpayers in the Intako region. The study employs a purposive sampling technique with a sample size of 100 respondents. Primary data is analyzed using Multiple Linear Regression in SPSS 25. The findings reveal that the implementation of the E-Billing and E-Filing systems as well as the decrease in final income tax rates significantly affect taxpayer compliance. This research contributes to the understanding of how technological advancements and tax policy changes can impact taxpayer behavior. The implications of the study suggest that governments and tax authorities should consider leveraging electronic systems and implementing tax rate reductions to enhance compliance among MSME taxpayers, leading to improved tax collection efficiency and overall revenue generation. Highlights: The study examines the impact of implementing the E-Billing System, E-Filing System, and reduced tax rates on the compliance behavior of MSME taxpayers. Findings indicate that the implementation of these systems and the decrease in tax rates significantly influence taxpayer compliance. The research highlights the potential benefits of leveraging electronic systems and implementing tax rate reductions to enhance compliance among MSME taxpayers and improve overall revenue generation. Keywords: MSME Taxpayers, E-Billing System, E-Filing System, Decreased Tax Rates, Compliance.